Pien Tze Huang Attenuates Neuro-inflammatory Injury in BV2 Microglial Cells Induced by Lipopolysaccharide via Inhibition of TLR4/MAPK Signaling Pathway - Zhenwei HUANG; Qing ZHANG; Lili HUANG; Xiaoqin ZHANG; Mingqing HUANG (康复学报)
Objective:To investigate the protective effect and the molecular mechanism of Pien Tze Huang (PZH) on Lipopolysaccharide (LPS) -induced neuro-inflammatory injury in BV2 microglial cells.Methods:BV2 microglial cells were cultured with RPMI-1640 medium supplemented with 10%fetal bovine serum and 1%penicillin/streptomycin at 5%CO2and 37℃in a humidified incubator. BV2 microglial cells were seeded at a density of 5×104cells/mL in 96-well plate. The inflammatory response in BV2 microglial cells was induced by LPS(100 ng/mL), while the cells were treated with different concentrations of PZH(0.05, 0.10 and 0.15 mg/mL) for 12 h. And then its absorbance at 490 nm was detected after the treatment of MTT for 4 h. BV2 microglial cells were seeded at a density of 5×104cells/mL in 24-well plate. The inflammatory response in BV2 microglial cells was induced by LPS(100 ng/mL), while the cells were treated with different concentrations of PZH(0.05, 0.10 and 0.15 mg/mL) for 12 h. Then supernatant was collected and the concentration of IL-6 was detected by enzyme-linked immunosorbent assay (ELISA) kit. BV2 microglial cells were seeded at a density of 1.6×105cells/mL in 6-well plate. The inflammatory response in BV2 microglial cells was induced by LPS(100 ng/mL), while the cells were treated with different concentrations of PZH(0.05, 0.10 and 0.15 mg/mL) for 12 h. Total RNA was extracted using TRIzol reagent and it was reverse-transcribed to synthesize the complementary DNA. And then the mRNA expression of IL-1β, IL-6 and TNF-α were determined using real time-qPCR. BV2 microglial cells were seeded at a density of 1.6×105cells/mL in 6-well plate. The protein extracts were isolated from each group of cells using RIPA protein lysis buffer after the administration of LPS(100 ng/mL) and different concentrations of PZH(0.05, 0.10 and 0.15 mg/mL) for 12 h. Then the protein expression of TLR4, ERK1/2, p-ERK1/2, p38, p-p38, JNK, p-JNK, COX-2, iNOS in BV2 microglial cells were detected by Western blot.Results:1) The result of MTT assay showed that PZH at 0.05-0.15 mg/mL concentration and LPS at 100 ng/mL concentration had no significant cytotoxicity on BV2 microglial cells (P> 0.05).2) The result of ELISA showed that the secretion of IL-6 was significantly increased in BV2 microglial cells induced by LPS compared with the normal control group (P< 0.001); compared with the LPS group, different concentrations of PZH significantly decreased the expression level of IL-6 in LPS-induced BV2 microglial cells (P< 0.05, P< 0.05, P< 0.01).3) The result of RT-qPCR showed that the transcriptional levels of IL-1β(P< 0.001), IL-6(P< 0.001) and TNF-α(P< 0.01) were significantly increased after the induction of LPS compared with normal controal group; different concentrations of PZH significantly inhibited the LPS-induced IL-1β(P< 0.05, P< 0.01, P< 0.001), IL-6(P> 0.05, P< 0.01, P< 0.001) and TNF-α(P< 0.01, P< 0.01, P< 0.001) mRNA upregulation.4) The result of Western blot showed that PZH significantly inhibited the LPS-induced TLR4/MAPK signaling pathway activation, and decreased the protein expressions of TLR4(P> 0.05, P< 0.05, P< 0.05), p-ERK1/2(P> 0.05, P< 0.05, P< 0.01), p-p38(P< 0.05, P< 0.01, P< 0.01), COX-2(P< 0.01, P< 0.01, P< 0.001) and iNOS(P< 0.01, P< 0.01, P< 0.01), but not p-JNK.Conclusion:PZH can significantly improve the LPS-induced neuro-inflammatory injury, which may be related to the inhibition of the activation of TLR4/MAPK signaling pathway.